Neuropsychological follow up in patients with Parkinson's disease, striatonigral degeneration-type multisystem atrophy, and progressive supranuclear palsy. Issue 3 (1st September 2000) - Soliveri, Paola; Monza, Daniela; Paridi, Dominga; Carella, Francesco; Genitrini, Silvia; Testa, Daniela; Girotti, Floriano
Abstract : OBJECTIVES: Impairment of executive function is frequent in Parkinson's disease (PD), striatonigral degeneration-type multisystem atrophy (SND), and progressive supranuclear palsy (PSP); sometimes frank dementia is also present. However, the progression of cognitive decline has not been adequately studied. The objectives were to delineate the progression of cognitive impairment in these parkinsonisms and to elucidate interdisease differences. METHODS: Twenty three patients with SND and 21 with PSP, referred consecutively, and 18 patients with PD matched for severity of parkinsonism were compared on a comprehensive battery of cognitive tests and motor invalidity scales. A mean of 21 months later (range 18–24 months) the patients were called for retesting. RESULTS: Only 12 patients with PD (66.6%), 14 with SND (60.8%), and 11 with PSP (52.4%) were retested; those who dropped out refused, had died, or were too disabled. The patients with PSP performed worse than patients with PD or SND in the short tale, verbal fluency, visual search, and Benton tests at first evaluation. Overall cognitive performance was similar in the PD and SND groups except that the SND group did significantly worse on the verbal fluency test. Between group comparison of changes in scores from first to second evaluation showed that patients with PSP deteriorated significantly in the Nelson test compared with patients with PD or SND, and that patients with PSP or SND declined significantly on the visual search test compared with patients with PD. There was no difference between the groups for motor decline. Two patients with PSP were demented (DSM IV criteria) at first evaluation and six at second evaluation; no patients with PD or SND were demented at either evaluation. CONCLUSIONS: The greater decline of patients with PSP in attention, set shifting, and categorisation abilities is probably related to the conspicuous frontal deafferentation associated with direct premotor and prefrontal involvement, and to dysfunction of the midbrain ascending activating system, known to occur in PSP.